Inside-Outside Circle Instructional Strategies with Image Media to Enhance Children Language Skills - Arya Wiradnyana, I Gd.; Ardiawan, IKN; Km. Agus Budhi A.P. (Jurnal Pendidikan Usia Dini, 2020)
Language skills are essential for early childhood, being able to speak clearly and process speech sounds, understand others, express ideas, and interact with others are the building blocks for a child's development. Therefore, this study will examine the effect of the Inside Outside Circle (IOC) instructional strategies with media images on children's language skills. This research is a quasi-experimental design with a posttest only and using a control group. The sample in this study were children in two kindergartens in the village of Banjar Tegal. Data analysis in this study was carried out by quantitative descriptive methods using t-test analysis techniques. The results of this study in kindergarten students in Banjar Tegal Village show that there is an influence of the IOC learning model with picture media on children's language skills (tcount = 6.28> ttable = 2.00). This shows that language skills achieved by groups of children participating in learning with the IOC model with drawing media are better than groups of children who attend learning without the IOC model. The implication is that further research is expected to develop other aspects of child devel- opment through the IOC model. Keywords: Children Language skills, Image media, Inside-Outside Circle Instructional Strategies Reference: Afrida, Ni., & Mahriza, R. (2019). Visual and Cognitive Media : The Language Acquisition of Children With Dyslexia in Aceh. IJLRES - International Journal on Language , Research and Education Studies, 3(1), 112–126. https://doi.org/10.30575/2017/IJLRES-2019010409 Al Otaiba, S., & Fuchs, D. (2006). Who are the young children for whom best practices in reading are ineffective? An experimental and longitudinal study. Journal of Learning Disabilities, 39(5), 414–431. https://doi.org/10.1177/00222194060390050401 Asrifan, A. (2015). The Use of Pictures Story in Improving Students’ Ability to Write Narrative Composition. International Journal of Language and Linguistics, 3(4), 244. https://doi.org/10.11648/j.ijll.20150304.18 August, Diane Shanahan, T. (2006). Developing Literacy in Second-Language Learners : Report of the National Literacy Panel on Language-Minority Children and Youth Edited by. Center for Applied Linguistics, 1–9. Barbot, B., Randi, J., Tan, M., Levenson, C., Friedlaender, L., & Grigorenko, E. L. (2013). From perception to creative writing: A multi-method pilot study of a visual literacy instructional approach. Learning and Individual Differences, 28, 167–176. https://doi.org/10.1016/j.lindif.2012.09.003 Bierman, K. L., Nix, R. L., Greenberg, M. T., Blair, C., & Domitrovich, C. E. (2008). Executive functions and school readiness intervention: Impact, moderation, and mediation in the Head Start REDI program. Development and Psychopathology, 20(3), 821–843. https://doi.org/10.1017/S0954579408000394 Blanden, J. (2006). ‘Bucking the trend’: What enables those who are disadvantaged in childhood to succeed later in life? Pensions, (31), 36. Cabell, S. Q., Justice, L. M., Piasta, S. B., Curenton, S. M., Wiggins, A., Turnbull, K. P., & Petscher, Y. (2011). The impact of teacher responsivity education on preschoolers’ language and literacy skills. American Journal of Speech-Language Pathology, 20(4), 315–330. https://doi.org/10.1044/1058-0360(2011/10-0104) Clark, R. C., & Lyons, C. (2011). Graphics for learning: Proven guidelines for planning, designing, and evaluating visuals in training materials (2nd ed.). San Francisco: CA: Pfiffer. Davoudi, A. H. M., & Mahinpo, B. (2013). Kagan Cooperative Learning Model: The Bridge to Foreign Language Learning in the Third Millennium. Theory and Practice in Language Studies, 2(6), 1134–1140. Dockrell, J. E., Stuart, M., & King, D. (2010). Supporting early oral language skills for English language learners in inner city preschool provision. British Journal of Educational Psychology, V ol. 80, pp. 497–515. https://doi.org/10.1348/000709910X493080 Dunlosky, J., Rawson, K. A., Marsh, E. J., Nathan, M. J., & Willingham, D. T. (2013). Improving students’ learning with effective learning techniques: Promising directions from cognitive and educational psychology. Psychological Science in the Public Interest, Supplement, 14(1), 4–58. https://doi.org/10.1177/1529100612453266 Gilles, G. (2015). Language Skills in Children: Development, Definition & Types. Retrieved from © copyright 2003-2020 Study.com. website: https://study.com/academy/lesson/language-skills-in-children-development- definition-types.html#transcriptHeader Gogtay, N., Giedd, J. N., Lusk, L., Hayashi, K. M., Greenstein, D., Vaituzis, A. C., ... Thompson, P. M. (2004). Dynamic mapping of human cortical development during childhood through early adulthood. Proceedings of the National Academy of Sciences of the United States of America, 101(21), 8174–8179. https://doi.org/10.1073/pnas.0402680101 Gutiérrez, K. G. C., Puello, M. N., & Galvis, L. A. P. (2015). Using pictures series technique to enhance narrative writing among ninth grade students at institución educativa simón araujo. English Language Teaching, 8(5), 45–71. https://doi.org/10.5539/elt.v8n5p45 Hadfield, J., & Hadfield, C. (2002). Simple Speaking Activities. Oxford: Oxford University Press. Haley, A., Hulme, C., Bowyer-Crane, C., Snowling, M. J., & Fricke, S. (2017). Oral language skills intervention in pre-school—a cautionary tale. International Journal of Language and Communication Disorders, 52(1), 71–79. https://doi.org/10.1111/1460-6984.12257 Hoff, E. (2013). Interpreting the Early Language Trajectories of Children from Low SES and Language Minority Homes: Implications for Closing Achievement Gaps. Developmental Psychology, 49(1), 4–14. https://doi.org/10.1037/a0027238.Interpreting Jin, S. H., & Boling, E. (2010). Instructional Designer’s Intentions and Learners’ Perceptions of the Instructional Functions of Visuals in an e-Learning Context. Journal of Visual Literacy, 29(2), 143–166. https://doi.org/10.1080/23796529.2010.11674678 Johanson, M., & Arthur, A. M. (2016). Improving the Language Skills of Pre- kindergarten Students: Preliminary Impacts of the Let’s Know! Experimental Curriculum. Child and Youth Care Forum, 45(3), 367–392. https://doi.org/10.1007/s10566-015-9332-z Justice, L. M., & Pence, K. L. (2004). Addressing the Language and Literacy Needs of Vulnerable Children: Innovative Strategies in the Context of Evidence-Based Practice. Communication Disorders Quarterly, 25(4), 173–178. https://doi.org/10.1177/15257401040250040201 Kagan, J., Reznick, J. S., & Snidman, N. (1987). The physiology and psychology of behavioral inhibition in children. Child Development, 1459–1473. Kamaliah, N. (2018). Applying The Inside-Outside Circle (IOC) Towards Students’ Speaking Abilityat The Second Grade of SMA Inshafuddin. Getsempena English Education Journal (GEEJ), 5(2), 106–115. Kleeman, D. (2017). Media exposure during infancy and early childhood: the effects of content and context on learning and development. Journal of Children and Media, 11(4), 504–506. https://doi.org/10.1080/17482798.2017.1375219 Krčelić, P., & Matijević, A. S. (2015). A Picture and a Thousand Words: Visual Tools in ELT. The International Language Conference on The Importance of Learning Professional Foreign Languages for Communication between Cultures 2015, 53(3/4), 110–114. Croatia. Lavalle, P., & Briesmaster, M. (2017). The Study of the Use of Picture Descriptions in Enhancing Communication Skills among the 8th- Grade Students--Learners of English as a Foreign Language. I.E.: Inquiry in Education, 9(1). Law, J., Rush, R., Schoon, I., & Parsons, S. (2009). Modeling Developmental Language Difficulties From School Entry Into Adulthood: Literacy, Mental Health, and Employment Outcomes. Journal of Speech, Language, and Hearing Research, 52(December), 1401–1416. Mayer, R. E. (2009). Multi-Media Learning : Prinsip-Prinsip dan Aplikasi. Yogyakarta: Pustaka Pelajar. NICHD. (2000). The relation of child care to cognitive and language development. National Institute of Child Health and Human Development Early Child Care Research Network. Child Development, 71(4), 960–980. Retrieved from http://www.ncbi.nlm.nih.gov/pubmed/11016559 Noble, C., Sala, G., Peter, M., Lingwood, J., Rowland, C., Gobet, F., & Pine, J. (2019). The impact of shared book reading on children’s language skills: A meta-analysis. Educational Research Review, https://doi.org/10.1016/j.edurev.2019.100290 28(September), 100290. Oades-Sese, G. V., & Li, Y. (2011). Attachment Relationships As Predictors Of Language Skills For At-Risk Bilingual Preschool Children. Psychology in the Schools, 48(7), 274–283. https://doi.org/10.1002/pits Pace, A., Alper, R., Burchinal, M. R., Golinkoff, R. M., & Hirsh-Pasek, K. (2019). Measuring success: Within and cross-domain predictors of academic and social trajectories in elementary school. Early Childhood Research Quarterly, 46, 112– 125. https://doi.org/10.1016/j.ecresq.2018.04.001 Pelli, D. G., Burns, C. W., Farell, B., & Moore-Page, D. C. (2006). Feature detection and letter identification. Vision Research, 46(28), 4646–4674. https://doi.org/10.1016/j.visres.2006.04.023 Perfetti, C. A., Liu, Y., & Tan, L. H. (2005). The lexical constituency model: Some implications of research on chinese for general theories of reading. Psychological Review, 112(1), 43–59. https://doi.org/10.1037/0033-295X.112.1.43 Puriniawati, N. K., Putra, M., & Putra, D. K. N. S. (2014). Penerapan Model Pembelajaran Inside Outside Circle Berbantuan Media Balok Untuk Meningkatkan. E-Journal PG-PAUD Universitas Pendidikan Ganesha, 3(1), 10. Purnamawanti, R., Hartati, S., & Sa’adah, S. (2015). Pengaruh Model Pembelajaran Kooperatif Tipe Inside Outside Circle Terhadap Kemampuan Berkomunikasi Siswa pada Materi Organisasi Kehidupan. Jurnal Program Studi Pendidikan Biologi ISSN, 5(11–22), 1689–1699. https://doi.org/https://doi.org/10.15575/bioeduin.v5i1.2459 Sadiman, A. S. (2002). Media Pembelajaran dan Proses Belajar Mengajar, Pengertian Pengembangan dan Pemanfaatannya. Jakarta: Raja Grafindo Persada. Segers, E., Perfetti, C. A., & Verhoeven, L. (2014). Foundations of Language, Literacy, and Numeracy Learning. International Journal of Disability, Development and Education, 61(3), 189–193. https://doi.org/10.1080/1034912X.2014.932555 Singh, C. K. S., Mei, T. P., Abdullah, M. S., Othman, W. M., Othman, W. M., & Mostafa, N. A. (2017). ESL LearnersâPerspectives on the Use of Picture Series in Teaching Guided Writing. International Journal of Academic Research in Progressive Education and Development, 6(4), 74–89. https://doi.org/10.6007/ijarped/v6-i4/3463 Singh, Y. K. (2005). Instructional Technology in Education. New Delhi: APH Publishing Corporation. Sumantri, M. S. (2015). Strategi Pembelajaran. Jakarta: Raja Grafindo Persada. Verhoeven, L., & Perfetti, C. A. (2011). Introduction to this special issue: Vocabulary growth and reading skill. Scientific Studies of Reading, 15(1), 1–7. https://doi.org/10.1080/10888438.2011.536124 Vitulli, P., Santoli, S. P., & Fresne, J. (2013). Arts in education: Professional development integrating the arts and collaborating with schools and community. International Journal of Pedagogies and Learning, 8(1), 45–52. https://doi.org/10.5172/ijpl.2013.8.1.45 Wahyuni, D. S., Mukhaiyar, & Kusni. (2013). Improving Student’s Speaking Skill by Using Inside-outside Circle Technique (At English For Teen Level 5, LBPP LIA, Pekanbaru). Jurnal English Language Teaching (ELT), 1(2), 17–29. Walter, O., Gil-Glazer, Y., & Eilam, B. (2019). ‘Photo-words’: promoting language skills using photographs. Curriculum Journal, 30(3), 298–321. https://doi.org/10.1080/09585176.2019.1568270 Zenkov, K., Ewaida, M., Bell, A., & Lynch, M. (2012). Seeing How to Ask First: Photo Elicitation Motivates English Language Learners to Write: Photos Prompt Middle Grades English Language Learners to Reflect upon and Write about Their Lives. Middle School Journal, 44(2), 6–13. https://doi.org/10.1080/00940771.2012.11461842 Zulminiati, & Hartati, S. (2019). Significant Sensory Stimulation Program Through the Use of Flash Card as Media of Toddler Language Development at Pre-Kindergarten. Advances in Social Science, Education and Humanities Research, 293(Nfeic 2018), 168–171. https://doi.org/10.2991/nfeic-18.2019.35